2020
DOI: 10.3892/or.2020.7816
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase A1 regulates breast cancer cell immunorecognition in a manner dependent on redox state

Abstract: Oxidoreductase protein disulphide isomerases (PDI) are involved in the regulation of a variety of biological processes including the modulation of endoplasmic reticulum (ER) stress, unfolded protein response (UPR), ER-mitochondria communication and the balance between pro-survival and pro-death pathways. In the current study the role of the PDIA1 family member in breast carcinogenesis was investigated by measuring ROS generation, mitochondrial membrane disruption, ATP production and HLA-G protein levels on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…siRNA transfection. Concentration of 5 µM of the siGENOME PDIA1 siRNA and 5 µM of the siGENOME non-targeting siRNA pool was added to each well containing 2x10 5 cells in DMEM and incubated for 72 h according to the suppliers' instructions (Dharmacon, UK) as described previously (4). The sequences of the siRNAs used are indicated as follows: siGE-NOME PDIA1-targeting siRNA pool: ACA GGA CGG UCA UUG AUU A, GGA CGG UCA UUG AUU ACA A, CCA AGAG UGU GUC UGA CUA, and CAGAGAGGAUCACAGAGUU; siGENOME non-targeting (scramble) siRNA pool: UAG CGA CUA AAC ACA UCA A, UAA GGC UAU GAA GAG AUA C, AUG UAU UGG CCU GUA UUA G, and AUG AAC GUG AAU UGC UCA A.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…siRNA transfection. Concentration of 5 µM of the siGENOME PDIA1 siRNA and 5 µM of the siGENOME non-targeting siRNA pool was added to each well containing 2x10 5 cells in DMEM and incubated for 72 h according to the suppliers' instructions (Dharmacon, UK) as described previously (4). The sequences of the siRNAs used are indicated as follows: siGE-NOME PDIA1-targeting siRNA pool: ACA GGA CGG UCA UUG AUU A, GGA CGG UCA UUG AUU ACA A, CCA AGAG UGU GUC UGA CUA, and CAGAGAGGAUCACAGAGUU; siGENOME non-targeting (scramble) siRNA pool: UAG CGA CUA AAC ACA UCA A, UAA GGC UAU GAA GAG AUA C, AUG UAU UGG CCU GUA UUA G, and AUG AAC GUG AAU UGC UCA A.…”
Section: Methodsmentioning
confidence: 99%
“…The PDI family member prolyl 4-hydroxylase β (P4HB, also known as PDIA1) functions as a chaperone that assists protein folding by inhibiting the aggregation of partially folded or damaged polypeptides (6). Recent findings have implicated PDIA1 in the processes of antigen processing and presentation, immunomodulation and tumor immunorecognition (4,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein disulfide isomerases (PDIs) constitute a superfamily of redox chaperones that participate in important cellular redox state processes, such as the modulation of cellular oxidative stress mediating homeostasis of the antioxidant glutathione [ 157 ], modulation of endoplasmic reticulum stress, the unfolded protein response, communication between endoplasmic reticulum and mitochondria, and the balance between cell proliferation and apoptosis [ 158 ]. A pulmonary fibrosis study showed that a domain of PDI (TXNDC5) was highly upregulated in patients with idiopathic pulmonary fibrosis as well as a mouse model of this injury, suggesting that this protein could be a novel therapeutic target in the treatment of pulmonary fibrosis [ 159 ].…”
Section: Introductionmentioning
confidence: 99%